Burden of hospital admissions caused by respiratory syncytial virus (RSV) in infants in England: A data linkage modelling study. Issue 6 (June 2019) - Reeves, R.M.; Hardelid, P.; Panagiotopoulos, N.; Minaji, M.; Warburton, F.; Pebody, R.
Highlights: Novel methodology using linked data to estimate the hospital burden of RSV. Detailed estimates of RSV-associated admissions and bed days in infants in England. RSV-associated admissions peaked in infants aged 6 weeks. RSV-associated admissions peaked in infants born September to November. Summary: Objectives: Current national estimates of respiratory syncytial virus (RSV)-associated hospital admissions are insufficiently detailed to determine optimal vaccination strategies for RSV. We employ novel methodology to estimate the burden of RSV-associated hospital admissions in infants in England, with detailed stratification by patient and clinical characteristics. Methods: We used linked, routinely collected laboratory and hospital data to identify laboratory-confirmed RSV-positive and RSV-negative respiratory hospital admissions in infants in England, then generate a predictive logistic regression model for RSV-associated admissions. We applied this model to all respiratory hospital admissions in infants in England, to estimate the national burden of RSV-associated admissions by calendar week, age in weeks and months, clinical risk group and birth month. Results: We estimated an annual average of 20, 359 (95% CI 19, 236-22, 028) RSV-associated admissions in infants in England from mid-2010 to mid-2012. These admissions accounted for 57, 907 (95% CI 55, 391-61, 637) annual bed days. 55% of RSV-associated bed days and 45% of RSV-associated admissions were in infants <3 months old. RSV-associated admissions peaked in infants aged 6 weeks, and those born September to November. Conclusions: We employed novel methodology using linked datasets to produce detailed estimates of RSV-associated admissions in infants. Our results provide essential baseline epidemiological data to inform future vaccine policy.